The problem of caste - Deshpande, Satish, Ed.; Deshpande, Satish (Hyderabad: Orient Black Swan, 2014)
Contributed articles; previously published in the Economic and political weekly.
Section 1. Disciplinary perspectives -- section 2. Caste and class -- section 3. Caste and politics -- section 4. Caste, state and law -- section 5. Caste and gender -- section 6. Contemporary explorations.
"EPW, Tata Institute of Social Sciences."
Includes bibliographical references.
Keywords: Caste -- India; Caste -- India; Caste -- India; Reverse discrimination -- India